Impulsivity-focused group intervention to reduce binge eating episodes in patients with binge eating disorder: study protocol of the randomised controlled IMPULS trial. Issue 12 (18th December 2015) - Schag, Kathrin; Leehr, Elisabeth J; Martus, Peter; Bethge, Wolfgang; Becker, Sandra; Zipfel, Stephan; Giel, Katrin E
Abstract : Introduction: The core symptom of binge eating disorder (BED) is recurrent binge eating that is accompanied by a sense of loss of control. BED is frequently associated with obesity, one of the main public health challenges today. Experimental studies deliver evidence that general trait impulsivity and disorder-specific food-related impulsivity constitute risk factors for BED. Cognitive-behavioural treatment (CBT) is deemed to be the most effective intervention concerning BED. We developed a group intervention based on CBT and especially focusing on impulsivity. We hypothesise that such an impulsivity-focused group intervention is able to increase control over impulsive eating behaviour, that is, reduce binge eating episodes, further eating pathology and impulsivity. Body weight might also be influenced in the long term. Methods and analysis: The present randomised controlled trial investigates the feasibility, acceptance and efficacy of this impulsivity-focused group intervention in patients with BED. We compare 39 patients with BED in the experimental group to 39 patients with BED in the control group at three appointments: before and after the group intervention and in a 3-month follow-up. Patients with BED in the experimental group receive 8 weekly sessions of the impulsivity-focused group intervention with 5-6 patients per group. Patients with BED in the control group receive no group intervention. The primary outcome is the binge eating frequency over the past 4 weeks. Secondary outcomes comprise further eating pathology, general impulsivity and food-related impulsivity assessed by eye tracking methodology, and body weight. Additionally, we assess binge eating and other impulsive behaviour weekly in process analyses during the time period of the group intervention. Ethics and dissemination: This study has been approved by the ethics committee of the medical faculty of Eberhard Karls University Tübingen and the University Hospital Tübingen. Data are monitored by the Centre of Clinical Studies, University Hospital Tübingen. Trial registration number: German Clinical Trials Register, DRKS00007689, 14/01/2015, version from 11/06/2015, pre-results.